Cloning and Expression of Thermomyces lanuginosus Phytase Gene in Pichia pastoris - Batool, Sada-e-; Rashid, Muhammad Hamid; Latif, Dr. Farooq (Journal of Basic and Emerging Sciences, 2024)
Phytase(myo-inositol-hexakisphosphate phosphohydrolase), (EC 3.1.3.8) has been inducted in local poultry feed mills and is of high value for better utilization of the inorganic phosphates and metals released from the complex sources of plant substrates. In this regard a locally isolated fungus Thermomyces lanuginosus which was known to produce thermostable enzymes and had earlier shown substantial clearance of Phytic acid on agar plates in these laboratories, was selected. The fungal phytase gene of size 1.5 kb from genomic DNA was PCR amplified and expressed in Yeast expression system of Pichia pastoris GS115. The phytase gene was cloned into the vector pPIC9K and confirmed through PCR and restriction digestion. Recombinant vector was linearized with pme1 and transformed into P. pastoris electro-competent cells. Methanol utilization fast (Mut+) selection was carried out on minimal methanol plates. Colony PCR resulted in the selection of four transformants. Recombinant resistant at 4 mg/ml of geneticin was selected as the potential phytase producing strain. It was further grown on minimal glycerol medium for inoculum and buffered methanol complex medium for the production of phytase. The crude enzyme showed 1.25 IU/mL phytase activity in shake flask. The kinetic parameters studied showed activation energy of 76.08 KJ/mol. The Km and Vmax were 0.091 mM and 0.074 U/mg. The recombinant P. pastoris phyS showed maximum activity at pH 4, and 40 ºC. The SDS-PAGE analysis showed a band of ∼54 kDa.